2014
DOI: 10.1039/c4ra02111h
|View full text |Cite
|
Sign up to set email alerts
|

Understanding thiol-induced etching of luminescent gold nanoclusters

Abstract: Electron injection from thiol ligands to Au8 clusters is a driving force for thiol-induced core etching of protein-stabilized Au8 clusters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 44 publications
1
23
0
Order By: Relevance
“…Based on the above observation, we optimized the conditions to get red luminescent clusters in high yield, which involved the following steps: (i) synthesis of the precursor Au 25 SBB 18 QCs, (ii) thermal treatment of Au 25 QCs for 24 h and addition of definite amounts of Au(I)SBB thiolate to the reaction medium at definite intervals and (iii) rapid cooling. [51][52][53][54][55][56] Core etching of nanoparticles/clusters in aqueous medium to form smaller clusters with luminescence are well known in the literature. Though a dampening of the characteristic absorption features of Au 25 clusters (black trace in Figure 1A) was observed for the redluminescent clusters (red trace), a distinct shoulder at 707 nm was observed in the case of the latter (see Figure S3).…”
Section: Resultsmentioning
confidence: 99%
“…Based on the above observation, we optimized the conditions to get red luminescent clusters in high yield, which involved the following steps: (i) synthesis of the precursor Au 25 SBB 18 QCs, (ii) thermal treatment of Au 25 QCs for 24 h and addition of definite amounts of Au(I)SBB thiolate to the reaction medium at definite intervals and (iii) rapid cooling. [51][52][53][54][55][56] Core etching of nanoparticles/clusters in aqueous medium to form smaller clusters with luminescence are well known in the literature. Though a dampening of the characteristic absorption features of Au 25 clusters (black trace in Figure 1A) was observed for the redluminescent clusters (red trace), a distinct shoulder at 707 nm was observed in the case of the latter (see Figure S3).…”
Section: Resultsmentioning
confidence: 99%
“…The fluorescence enhancement possibly results from the charge transfer via the Ag-S bonds (from the ligands to the metal center) or from the change of the microenvironment [26,27]. The fluorescence reduction of dC 12 -AgNCs in high concentration of thiol compounds may be due to the etching of dC 12 -AgNCs induced by the large amount of thiol compounds [40]. Therefore, to balance the etching effect, the optimal concentration of the peptide substrate was chosen as 200 nM.…”
Section: Resultsmentioning
confidence: 99%
“…The high concentration of ALP, lysozyme, and thrombin cannot cause the observable fluorescence recovery of the dC 12 -AgNCs-peptide/GO complex at the same conditions. The etching effect of dC 12 -AgNCs [40,44] induced by large amount of lysozyme might produce a large decrease in signal. The different fluorescence patterns (turn-on or turn-off) of AgNCs in responses of thiol compounds have been reported [26,27,45].…”
Section: Resultsmentioning
confidence: 99%
“…An important role in luminescence is also played by the nature of the ligand. 305,306 Recent experimental studies on the temperature dependence of luminescence in Au 38 (SR) 24 showed that emission occurs at higher energies compared to the energy of the absorbed quantum. 118 However, the mechanism of filling of highly excited states is to be clarified.…”
Section: Clusters As Quantum Dotsmentioning
confidence: 99%